ANALISIS KUALITAS PELAYANAN PUBLIK DI DINAS KESEHATAN KABUPATEN SUMBAWA - APRIANSYAH, ALDI; SUPRIADI, DEDI (Universitas Mahasaraswati K. Mataram, 2024)
The government has guaranteed good publik health starting from a clean, healthy environment and developing into adequate facilities. The health service, as an intermediary for health workers, must of course have adequate facilities to provide services to the community. This research was conducted at the Sumbwa District Health Service, Wast Nusa Tenggara Province using qualitative methods. The aim of this research is to determine the quality of the health service office in running the public service system. The results of this research ore determined by indicator such as Tangibles (Direct evidence), Reliability (Reliability), Responsiveness (Responsiveness), Assurance (Guarantee), Empathy (Empathy)The results of this research including the direct evidence point, there are advantages and disadvantages, including clear service information signs, a comfortable waiting room, but it still has shortcomings such as a hole in the roof, untidy parking. Meanwhile, on the point of reliability, employees are reliable in providing services, then the ability to master electronic goods at work. The point of responsiveness is that employees carry out work according to procedurs, customer dont wait long. Guarantee point, the employees provide service politely, friendly and with a smile. Employees also provide detailed explanations regarding problems faced by customers. Lastly, empathy, some employees still differentiate between customers based on relatives or acquaintances. This is usually done by contract employees.